Laus Platonici philosophi: Marsilio Ficino and his influence - Forshaw, Peter J.; Rees, Valery; Clucas, Stephen (Brill's studies in intellectual history 0920-8607, 2011)
Acknowledgements; Notes on Contributors; Introduction; Part I The Philosophy of Marsilio Ficino; Ficino and the God of the Platonists; Monstrous Melancholy: Ficino and the Physiological Causes of Atheism; Quo vertam oculos ut te laudem? Aspects of Praise in Ficino's Writing; The First Pico-Ficino Controversy; 'Et nuper Plethon'--Ficino's Praise of Georgios Gemistos Plethon and his Rational Religion; Zoroaster and the Flying Egg: Psellos, Gerson and Ficino; 'Jupiter tames Saturn': Astrology in Ficino's Epistolae; Ficino's Hymns and the Renaissance Platonic Academy.